Toward industrial democracy : - Odaka, Kunio (Harvard University Press, 1975)
Kunio Odaka is Japan’s leading labor sociologist. In this study he discusses the complex attitudes of Japanese workers toward management, unions, work, and leisure. The results of his scholarly surveys indicate a trend toward the democratization of Japanese industrial management. In part, the book is a presentation of Odaka’s belief in the necessity for greater worker participation in the decisions that affect their working lives, a belief that is indeed radical in the Japanese setting.